Typical Mistakes in Forensic Examinations on Disputes Related to Child-Rearing - E. V. Vaske; F. S. Safuanov; T. N. Sekerazh (Теория и практика судебной экспертизы, 2020)
The article analyses errors when appointing and conducting a forensic examination of disputes related to children’s upbringing. When summarizing expert practice in this category of civil cases (based on the study of 97 expert opinions on forensic psychological examination), the most significant errors were identified: incorrect determination of the type of expertise (including the appointment of psychological and pedagogical expertise which does not have a methodological basis as forensic examination), non-compliance with the qualification requirements to a forensic expert and, as a result, the introduction of an improper subject of forensic expert activity into the judicial process, an expert’s going beyond the limits of specialized knowledge and procedural powers, the incompleteness of research, the use of invalid research methods and techniques, and other methodological violations, associated with the incorrect assessment of the results of psychological diagnostics, inaccurate phenomenological analysis of essential phenomena of child-parent relations.Considering that due to the facts to be proved are essential for deciding on a case, the expert’s opinion is of particular importance and can significantly affect the formation of the court’s inner conviction, which means that expert errors significantly increase the risk of judicial errors. The article substantiates the urgent necessity of the early enactment of a legal act regulating experts’ responsibility for the level of their qualifications and setting professional requirements to experts.